Investigation Of Encapsulant Discoloration Mechanism In UV/Blue Light-Emitting Diode With Copper Hybrid Particles Filler Using Taguchi Method - Christina Chin, Kai Qi (Universiti Sains Malaysia, 2022)
Titanium dioxide (TiO2) particles is known to be a promising semiconductor due to its high performance in photocatalytic applications. However, with prolonged exposure to ultraviolet (UV) light, it loses its stability. This project focus on the photocatalytic performance of copper hybrid (Cu/TiO2) particles where the encapsulant discoloration mechanism in UV/Blue Light-Emitting Diode (LED) can be improved by incorporating Cu/TiO2 particles in the LED as the filler. Copper (Cu) was deposited on the surface of TiO2 particles through impregnation method assisted by UV radiation and the effect of three synthesis parameters i.e. concentration of Cu2+ ions, irradiation time and annealing temperature were studied. The structural and morphological analysis indicated that the deposition of Cu on the surface of TiO2 particles. It was shown that the Cu/TiO2_1 particles (synthesized with 300 ppm of Cu2+ ions, 120 minutes of UV irradiation and annealing temperature of 550 °C) has the lowest rate constant (k) of 0.000278 min-1 and photodegradation efficiency (PE) of 3.44098 % at 120 minutes. The optimization of synthesis parameters was employed via Taguchi method to achieve poorest photocatalytic degradation of Cu/TiO2 particles. The finding shows that the optimal synthesis parameters obtained were 300 ppm of Cu2+ ions, 0 minute of UV irradiation and annealing temperature of 400 °C. Furthermore, the yellowing effect after exposure under UV irradiation was observed and it is found that the yellowing effect on the thin silicone film incorporated with Cu/TiO2 particles were lesser as compared to the thin silicone film incorporated with TiO2 particles. As a result, Cu/TiO2 particles can reduce the photodegradation activity that may cause the polymeric material in the LED encapsulant being degraded through chain scission and turned yellowish. Therefore, it is said that Cu/TiO2 particles can be embedded in the LED encapsulant as filler to reduce the photocatalytic degradation as well as achieve greater light extraction efficiency (LEE).